2007
DOI: 10.1002/jmor.10532
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of body‐wall muscle differentiation during embryonic development of Enchytraeus coronatus (Annelida: Oligochaeta; Enchytraeidae)

Abstract: The plesiomorphic arrangement of body-wall musculature within the annelids is still under discussion. While polychaete groups show a great variety of patterns in their somatic muscles, the musculature of soil-living oligochaetes was thought to represent the characteristic pattern in annelids. Oligochaete body-wall muscles consist of an outer continuous layer of circular and an inner continuous layer of longitudinal muscles, forming a closed tube. Since designs of adult body musculature are influenced by evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 59 publications
5
24
0
Order By: Relevance
“…The same situation was described for several species of Sipuncula (Wanninger et al, 2005;Schulze and Rice, 2009;Kristof et al, 2011). In most other annelids, the circular muscle fibers appear in an anteroposterior direction, which might represent the ground pattern of muscle formation in annelid trochophores (Seaver et al, 2005;Bergter and Paululat, 2007;Bergter et al, 2008;Wanninger, 2009;Helm et al, 2013). Summarizing, we find that the nervous system and the body musculature of this stage already resemble that of adult individuals in terms of complexity.…”
supporting
confidence: 82%
“…The same situation was described for several species of Sipuncula (Wanninger et al, 2005;Schulze and Rice, 2009;Kristof et al, 2011). In most other annelids, the circular muscle fibers appear in an anteroposterior direction, which might represent the ground pattern of muscle formation in annelid trochophores (Seaver et al, 2005;Bergter and Paululat, 2007;Bergter et al, 2008;Wanninger, 2009;Helm et al, 2013). Summarizing, we find that the nervous system and the body musculature of this stage already resemble that of adult individuals in terms of complexity.…”
supporting
confidence: 82%
“…This antero‐posterior pattern is known for many other annelids as well (Seaver et al. ; Bergter & Paululat ; Bergter et al. ; Wanninger ; Helm et al.…”
Section: Discussionsupporting
confidence: 59%
“…as in E. coronatus , except for those at the ventral side of the embryo. In E. coronatus , the ventral primary longitudinal muscles of either side merge at the ventral midline during the movement of the ventral nerve cord into its position within the coelomic cavity (neurulation), closing the homogenous muscle layer (Bergter and Paululat 2007). Hence, there are no secondary longitudinal muscles formed at the ventral side of the E. coronatus embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial investigation of muscle differentiation in the terrestrial oligochaete Enchytraeus coronatus (Enchytraeidae, Fig. 1) revealed that patterns in the somatic musculature during embryogenesis are similar to those found in adult polychaetes (Bergter et al 2004; Bergter and Paululat 2007). Therefore, we propose that an examination of muscle patterns in developing stages will have a significant impact on our understanding of the muscle arrangement of the annelida (Purschke and Müller 2006; Bergter and Paululat 2007).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation